Enhanced Decision Making Using Multi Factor Evaluation Process for Innovative Product Selection - Ibnu Rivansyah Subagyo; Putri Taqwa Prasetyaningrum (IJCONSIST JOURNALS, 2024)
The process of selecting innovative products can be complex and challenging due to the multiple factors involved. This study explores an enhanced decision-making approach using the Multi-Factor Evaluation Process (MFEP) to assist in selecting the most suitable product among alternatives. The MFEP methodology evaluates products based on various criteria and assigns weightings to each factor according to its significance. In this research, three innovative products—SkyWater, HORNET, and BPP-4D—are evaluated. The evaluation considers critical performance indicators and calculates a final score for each product. The results indicate that SkyWater has the highest evaluation score, followed by HORNET and BPP-4D, providing insights into their relative suitability for recommendation. This paper demonstrates the effectiveness of the MFEP in facilitating objective decision-making in the selection of innovative products.